Using Bulletin Boards in an Educational Setting. - Dos Santos, Brian L.; Wright, Andrew L. (Communications of the ACM, 2006)
This article examines the benefits associated with the use of threaded message postings systems, also known as online bulletin boards. Many organizations utilize these boards to share information with customers, suppliers, and employees and to provide support services. Bulletin boards can be integral in distance education and traditional classroom-based teaching. They can be used to discuss cases or readings, to communicate with and among participants, and to increase the productivity of group assignments.